Changing Pattern of Dengue Virus Serotypes in Thailand between 2004 and 2010 - Pongsiri, Piyathida; Themboonlers, Apiradee; Poovorawan, Yong (Journal of Health, Population and Nutrition, 2012)
Dengue virus infection is a major concern in several countries, and more than 50 million people are infected worldwide each year. Thailand is one of the countries where people are susceptible to infection due to favourable geographical and environmental conditions. In this retrospective study, we reported the changing pattern of dengue virus serotypes during the period between 2004 and 2010. The following percentage prevalence showed different serotypes of dengue virus (DENV) predominant in respective years: DENV1 in 2004 (56.41%), DENV4 in 2007 (50%), DENV1 in 2008 (57.41%), and DENV3 in 2010 (38.7%). Moreover, the major serotypes were not stable as they showed a shift from one serotype to another. We also found co-infection with two different serotypes and reported the clinical manifestations, which were not different from infection with a single serotype. Co-infection with various serotypes may not necessarily cause more severe disease. DOI: http://dx.doi.org/10.3329/jhpn.v30i3.12300 J HEALTH POPUL NUTR 2012 Sep;30(3):366-370